Kinetic Features of Hexene‐1 Polymerization over Supported Titanium–Magnesium Catalyst. Issue 9 (18th June 2014) - Echevskaya, Ludmila; Matsko, Mikhail; Nikolaeva, Marina; Sergeev, Sergei; Zakharov, Vladimir
Abstract The data on the effect of cocatalyst composition and polymerization conditions on activity and MWD of polyhexene (PH) produced over a high‐activity titanium‐magnesium catalyst are obtained. The cocatalyst has an extremely strong effect on the MWD of polyhexene. When triisobutylaluminum is used as a cocatalyst, PH with high Mw and narrow MWD is produced. The use of TEA decreases the Mw of PH and broadens the MWD. It is found the ratio between the rate constant of chain transfer to TEA (ktrAl) and the propagation rate constant (kp) is two orders of magnitude higher than the ktrAl/kp value calculated for polymerization of ethylene and propylene. We attributed this effect to formation of polyhexene in the solution, as opposed to polymerization of ethylene and propylene in slurry polymerization. The addition of hydrogen at polymerization of hexene‐1 significantly increases activity and stereospecificity.<inline-graphic xlink:href="ark:/27927/pgh17zztsvq" content-type="mren201400009-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />